Reproducibility of Running Anaerobic Sprint Test for soccer players - De Andrade, Vitor L.; Pereira Santiago, Paulo R.; Kalva Filho, Carlos A. [UNESP]; Zapaterra Campos, Eduardo [UNESP]; Papoti, Marcelo (Edizioni Minerva Medica, 2016)
BACKGROUND: Although the Running Anaerobic Sprint Test (RAST) presents reliability when performed on firmer surfaces (i.e. athletic track), its application on less rigid surfaces can compromise the measure determinations. Thus, the aim of the present study was to evaluate the RAST reliability for soccer players performing on grass, and wearing soccer cleats. METHODS: Fourteen soccer players (16 +/- 1 years, 72.3 +/- 10.3 kg, 177.2 +/- 8.4 cm, 14.5 +/- 5.3% of fat mass, and VO2MAX of 52.0 5.1 mL.kg-1.min-1) performed six maximal 35-meter effort interspersed by 10s of passive rest (RAST). After 48h the RAST was repeated to test the reliability. The main variables analyzed were the peak power (PP), mean power (MP), fatigue indexes (FI), and impulse (ImP). The reproducibility of test and re-test was tested through the Student's t Test to paired samples, intraclass correlation (ICC), typical error (TE), and coefficient of variation (CV%). RESULTS: The PP (test=701.4 +/- 169.5 W; re-test 712.4 +/- 142.3 W), MP (test=538.6 +/- 111.4 W; re-test=551.9 101.1 W), and the ImP (test=2841.2 +/- 461.8 N.s; re-test=2797.2 +/- 575.9 N.s) were not different, presented significant correlation between the. situations (ICC=0.88; 0.96 e 0.93; respectively), and low values of TE (71.9 W; 30.6 W e 191.1 N.s, respectively) and CV% (10.2%; 5.9% e 6.8%, respectively). The FI (test=40.1 +/- 5.8; re-test=38.7 +/- 7.7%) were not significantly related between the test and re-test, and presented high TE (5.7%) and CV% (14.4%). CONCLUSIONS: We can conclude that RAST presents high reliability when performed on grass with soccer cleats, just as rigid surfaces. Besides, the ImP is more robust than the.
Keywords: Soccer; Exercise; Anaerobic threshold